PERANCANGAN DAN PEMBUATAN APLIKASI EDITOR NASKAH FILM ATAU DRAMA BERORIENTASI PADA ELEMEN-ELEMEN NASKAH - Gogo Tio Pandang Tambunan; Gregorius Satia Budhi; Djoni Haryadi Setiabudi (Jurnal Infra, 2014)
Standarization Play became the unwritten benchmark for professional industry of Film Making or Theater Performance. But, the creating of Standarization Stageplay or Screenplay sometimes be a problem for novice scriptwriters in starting their career. The applications can help the novice scriptwriter is less able to sustain these constraints. Based on the background of the problem, The Author designed an application that can help the beginner to create a standar script.This application adds the convenience that is not offered similar applications as well as added features that fit the needs of scriptwriters. The Author used Java Swing GUI technology to implement anything that The Author have been researched about either Screenplay or Stageplay.Based on the test results, this application can compete with other scriptwriting application.